Unchanging public order policing in changing times in East Africa. Issue 3 (10th August 2015) - Baker, Bruce
ABSTRACT This article offers a political analysis of the practices and motives of public order policing in Ethiopia and Uganda. It offers an explanation of the continuation of forceful tactics against political protest in a context of changing methods of information gathering, organisation and mobilisation by urban activists resulting from their access to internet and communication technology. It finds the two regimes, as anocracies, are caught between legally allowing protest and yet, conscious of their fragility, determined to crush opposition. For the latter approach, their militarist leaderships rely heavily on continued police violence. The paper concludes that failure of the police to adapt their public order policing to the new protest environment leaves them increasingly ineffective and unpopular. It is likely to provoke an escalation of violence and may both undermine the legitimacy of their regimes and reverse their attempts to open political space that justified their rebellions against former autocracies.